IITA-Gender Responsive Breeding Training Report - Cavicchioli, M.; Zimbiti, T.; Teeken, B.; Nwanze, D.O.; Liani, M.; Parkes, Elizabeth Y.; Bello, A. (International Institute of Tropical Agriculture, 2023)
On September 21st, 2022, scientists from various African countries specializing in plant breeding for cassava, yam, cowpea, maize, soybean, and plantain were welcomed to the International Institute of Tropical Agriculture (IITA) in Ibadan for a three-day training on Gender Responsive Breeding. The primary goal of this training was to highlight the significance of gender and social inclusion in plant breeding research. The training provided an introduction on the definition and the application of gender- and social inclusion concepts to the breeding pipeline's design and implementation. It also enabled the trainees to recognize the relationship between gender issues and trait preferences, assess the social impact of breeding research activities, and, most importantly, to appreciate the benefits of working in an interdisciplinary team that combines biophysical and social scientists. The use of interactive learning methods throughout the training allowed trainees to participate, voice their opinions, exchange ideas, and feel equally involved. Supported by in-person participation, such techniques were intended to allow participants to vividly notice and appreciate the growth of their knowledge in gender responsive breeding through an ongoing reflection of the notions and approaches learned in their everyday breeding work. In general, the training was well appreciated by the participants, many of which expressed interest in a follow-up. According to many participants, the richness of the content presented would have required devoting more time to the group exercises and discussions. A short video documentary of the training with highlights from some of the participants is available at this link: https://www.youtube.com/watch?v=x9_Plq6WenA